Development of Sugar Free Riceberry Pearl Enriched with Dietary Fiber - Sukkhown, Pattraporn; Mupattararot, Kungsadarn (Journal of Food Technology, Siam University, 2024)
The research aimed to develop healthy pearls from riceberry rice by selecting the basic formula and studying the appropriate ratio of using riceberry flour as a substitution for tapioca flour at 5 levels, namely 0:100, 25:75, 50:50, 75:25, and 100:0, varying the pearl boiling time at 35, 40 and 45 minutes. The results showed that when increasing the amount of riceberry flour and boiling it for a longer period of time, the hardness and springiness of the pearls decreased. The appropriate ratio was 25:75 (riceberry flour: tapioca flour) by boiling time the pearls for 40 minutes, with the highest overall liking score. The study of the amount of konjac to increase dietary fiber in riceberry rice pearls at the levels of 0, 5 and 10 percent found that the appropriate level was 10 percent. The addition of konjac made the pearls have a tougher and chewy texture with increased springiness (1.42N) and gumminess (3.21N) values from the control sample. The formulation development by studying the ratio of sucralose, a sweetener, and a substitute of brown sugar. The results found that sucralose at 0.42 percent (percentage by weight) could be used in place of 100 percent brown sugar in the control formulation. The amount of reduced sugar was 5.84 g/100g, which was approximately 3 times less than the control sample (16.50 g/100g). In addition, the developed formula had a moisture content of 23.85%, 0.30% ash, 2.10% protein, 0.95% fat, 2.12% crude fiber, and 70.68% carbohydrates, with microbial quality and all yeasts and molds at 0 cfu/g. The testing by 200 consumers of developed healthy pearls from riceberry rice, found that 94% of consumers accepted the product and 92% were interested in purchasing the product.